Kesantunan Berbahasa dalam Pembelajaran di Kelas IX SMPN 2 Sungguminasa - Sakaria, Sakaria; Usman, Usman; Nurfaizah, Nanni (Nuances of Indonesian Language, 2024)
This study aims to describe the form of language politeness in Indonesian language learning in class IX of SMPN 2 Sungguminasa. This research applies descriptive qualitative research method.  The data of this research is in the form of spoken language taken from conversations that occur in the interaction between students and teachers during the discussion process in Indonesian language learning. The data sources in this research are teachers and students of class IX SMPN 2 Sungguminasa. The collected data were processed through qualitative descriptive analysis approach. The results show that the politeness form of teacher-to-student interaction in Indonesian language learning in class IX, namely obeying 5 forms of maxims, namely, the maxim of wisdom, the maxim of generosity, the maxim of respect, the maxim of agreement, and the maxim of sympathy. Furthermore, the principle of politeness that is violated is the maxim of humility by students.